COMPARATIVE IN VIVO EFFICACY OF ORAL FORMULATIONS OF IVERMECTIN AND LEVAMISOLE AGAINST NATURAL HELMINTH INFECTION IN SMALL RUMINANTS - S. Ahmad; M. S. Sajid; R. Tabassum; R. M. Siddique; M. Imran; M. A. Malik (Journal of Animal and Plant Sciences, 2020)
This study was conducted to investigate the distribution of gastrointestinal (GI) parasites and their control in sheep and goats of the three villages of Faisalabad, Pakistan. Faecal samples (n=347 each) were analyzed through McMaster egg counting technique. The comparative efficacy of the oral formulations of ivermectin (KEPROMAC ORAL® Holland) and levamisole (Nilverm® Pakistan) was evaluated at the recommended doses. Faecal samples were obtained directly from the recta at 1st, 7th, 14th and 21st day after treatment. The overall prevalence of the GI parasites was 81.27% in sheep and 54.47% in goats. Intrinsic determinants like age, sex and breed were found significantly (P≤0.05) associated. Among various husbandry practices; grazing, hygienic conditions, housing systems, floor pattern and animal keeping system have shown significant effects (P≤0.05). The post treatment Faecal Egg Count Reduction Test (FECRT) indicated reduction of eggs up to day 14 followed by increase at 21st day in both species. The efficacy of ivermectin was higher as compared to levamisole-treated group. However, the treated groups indicated significant reduction as compared to un-treated control. The study provided the better choice of drug for preventive and/or therapeutic management of GI parasitism in sheep and goat populations of the selected villages of Faisalabad district, Punjab, Pakistan.
Keywords: Gastrointestinal parasitism; sheep; goat; epidemiology; anthelmintic efficacy; intrinsic determinants